KESETARAAN PELAYANAN PUBLIK BAGI NARAPIDANA PENYANDANG DISABILITAS - Subroto, Mitro; Laode, Priyan Alif Muzani Atiri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Equality in public services for inmates with disabilities in prisons is a crucial issue that requires attention. This study aims to examine the implementation of equal public services for inmates with disabilities in prisons, focusing on aspects such as accessibility, reasonable accommodation, and non-discrimination. The research method employed is qualitative, involving interviews with prison officials, inmates with disabilities, and relevant stakeholders. The findings suggest that while efforts have been made to provide equal services, there are still challenges in ensuring full accessibility and reasonable accommodation for inmates with disabilities. The study concludes with recommendations for improving the implementation of equal public services in prisons to better protect the rights and dignity of inmates with disabilities.Keywords: equality; public services; inmates with disabilities; prisons; accessibility.